Political Factors Influencing the Shortage of Human Resources for Health in Samburu County Referral Hospital, Kenya - Omambia, Salim M.; Nganga, Nipher Khisah (Advances in Social Sciences Research Journal, 2022)
Objective: The principal reason for carrying out the project was to determine the political factors that influenced the shortage of human resources for health at Samburu County Referral Hospital in Kenya. Design setting: The investigation deployed a cross-sectional study. Subjects or participants: A sample population of 145 participants was calculated using the Fishers et al method of 1998. Data collection was done using a survey with closed-ended queries. A strict inclusion criterion was followed to select the respondents from all trained health personnel in Samburu County Referral Hospital in Kenya. Data were analyzed using SPSS, presented in figures with various diagrams like charts and tables and interpreted using descriptive statistics. Results: The results showed that according to the study, there were no programs set aside to ensure that all employees in the hospital were treated fairly. When it came to discharging their jobs especially posting, 72.6% (p-value 0.000 and OR 1.1), agreed that they gave bribes to be posted to their preferred working station. Segregation among the healthcare workers had been reported with 59.4% and 56.8% (p-value 0.00 and OR 1.1), of the healthcare workers agreeing that there was segregation by virtue of their religion, gender and culture. Conclusion: Political factors such as employees using their affiliate influence to get better working stations, preferential treatment and job posting were among the major issues highlighted in the study.